Industrial decarbonisation oriented distributed renewable generation towards wastewater treatment sector: Case from the Yangtze River Delta region in China. (1st October 2022) - Xu, Jiuping; Zhao, Chuandang; Wang, Fengjuan; Yang, Guocan
Abstract: Using the floor area in the wastewater treatment sector to deploy distributed renewable energy is economical and can assist in industrial decarbonisation; however, little attention has been paid to study of the ideal capacity. This study proposes a grid-connected wind-solar-storage system scheme for retrofitting existing wastewater treatment plants (WWTPs) and explores its regional potential. Seven treatment scales of WWTPs are classified, and the electricity consumption and available layout areas are estimated using fuzzy numbers. A multi-objective model with economic, technological, and environmental considerations is built and then solved using the ϵ -constraint method. A case study in the Yangtze River Delta region in China is conducted to demonstrate the effectiveness of the proposed method. Results show that the installed capacity is 5.9 GW and that the levelized cost of electricity in the seven categories reflects a ' V ' shape. The regression equations of the optimal potential, treatment scale, and layout area are identified. Further, scenarios in which export to the main grid is permitted and not permitted are discussed, and a four-step implementation strategy is proposed. This study provides an effective method for governments to improve space utilisation and energy decarbonisation in the industrial sector. Highlights: A renewable energy retrofitting scheme for wastewater treatment plants is proposed. An analysis paradigm and optimisation model are used to explore regional potential. The method's practicality and efficiency are proved in Yangtze River Delta. Different treatment scales and implementation strategies are presented.